RESPONSE OF GROWTH AND YIELD OF THREE VARIETY OF SOYBEAN (Glycine max [L] Merr.) ON SOME AVAILABLE SOIL WATER DEPLETIONS - Wawan Setiawan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
The aims of this research was to find out the effect of available soil water depletion on the growth andyield of three varieties of soybean (Glycinemax [L]Merr.). This study used a factorial ina completely randomizeddesign (CRD)with 2 factors, namely factor I (Available soilwater depletion fraction, p) and Factor II (Variety, V).Each treatment consisted of 3 levels, factor I consists of P1(0.2), P2(0.4) and P3(0.6) of available soil waterdepletion, and factors II consists of three variety,Wilis (V1), Kaba (V2) andTanggamus (V3), with repeats 3 times.Reference evapotranspiration measurements on P(0.2) is done using the grass plant. The results showed thattreatment of available soil water depletion fraction (p), varieties, and their interactions were not significantlydifferent, on the growth and production. All three varieties of plant did not experience stress during growth anddevelopment stage until harvest. The highest productionwas inTanggamus varieties (V3) in P1(0.2) of 17.86 g/potwith a total of 80.430 ml of irrigation water, followed by Kaba (V2) on P1(0.2) 15.23 g/pot with total irrigationwater 75.800ml andWillis (V1) on P3(0.6) 14.96 g/potwith a total of 75.600ml of irrigationwater. The smallerof available soil water depletion fraction the higher of evapotranspiration (ETc). Crop yield response factor towater (Ky) greater than 1 (Ky>1), this means that the decrease of relative production larger than decrease ofrelative evapotranspiration.